Answer:
3Ag⁺ + 3NO₃⁻ + 3Na⁺ + PO₄³⁻ → Ag₃PO₄(s) + 3Na⁺ + 3NO₃⁻
Step-by-step explanation:
An ionic equation is a chemical equation where the electrolytes in aqueous solution are expressed as dissociated ions.
For the reaction:
3AgNO₃(aq) + Na₃PO₄(aq) → Ag₃PO₄(s) + 3 NaNO₃(aq)
AgNO₃(aq), Na₃PO₄(aq) and NaNO₃(aq) are dissociated in water thus:
AgNO₃(aq) → Ag⁺ + NO₃⁻
Na₃PO₄(aq) → 3Na⁺ + PO₄³⁻
NaNO₃(aq) → Na⁺ + NO₃⁻
The ionic equation is:
3Ag⁺ + 3NO₃⁻ + 3Na⁺ + PO₄³⁻ → Ag₃PO₄(s) + 3Na⁺ + 3NO₃⁻
I hope it helps!